Carbon stock, subsurface characteristics and accommodation settings of sub-tropical peatland Histosols, K'gari, Queensland Australia - Chalmers, Gareth; Ghasemzadeh, Zeinab; Chittleborough, David; Gontz, Allen; Cooray, Iroshaka Gregory; Yule, Catherine; Chellaiah, Darshanaa; McCallum, Adrian (Geoderma Regional, 2025)
Whereas temperate and tropical peatlands have been extensively studied, much less is known about the age, formation history, carbon stock and soil characteristics of subtropical peatlands. Here we investigate the organic carbon density or stock and soil characteristics of three peatlands of K'gari (Fraser Island), Queensland, Australia. The Empodisma minus -dominated peatlands are unique to the subtropics and their bulk density, pH, oxidation-reduction potential, carbon percentages and carbon stocks were compared to other Empodisma sp. peatlands in temperate and montane-alpine climates as well as global peatland estimates. A good agreement occurs between the elemental analyser (LECO) derived carbon percentages and the estimations made by loss-of-ignition-derived carbon percentages using Farmer et al. (2014) conversion factor. Carbon stock estimation ranges between 381.2 and 1665.5 Mg C ha−1 for the total peat depth and ranges between 444.0 and 1189.7 Mg C ha−1 on a per metre basis. The carbon stock average for the Moon Point and Dilli Swamp peatlands is comparable to global peatland estimates with the Red Lagoon peatland is lower than the average. All three peatlands have a higher average carbon stock than other Empodisma-dominated peatlands in temperate and montane-alpine climates. The three peatland sites chosen are within different morphosequences that range in age between Holocene, 7.8 to 132 ka and 132–263 ka. The Moon Point peatland (Holocene; < 11,700 BP) has a higher bulk density, lower moisture content and higher degree of humification compared to the other morphosequence areas. The difference in peat characteristics is not due to the morphosequence, as the climate changed approximately 6000 to 5000 years BP to be more favourable for peat accumulation across south-east Queensland. However, we suspect the older morphosequence (i.e., Yankee Jack) as well as the Holocene coastal sediment setting, due to their lower topography reduces the groundwater level and the accommodation space for peats to accumulate. The lower accommodation setting limits the peat thickness, increases the number of hiatuses and is susceptible to more peat fires. This study shows the K'gari peatlands are significant carbon sinks and careful management is needed to ensure they do not become carbon emitters as climate continues to change.